A comprehensive review of experimental evaluation methods and results of polymer micro/nanogels for enhanced oil recovery and reduced water production. (15th September 2022) - Liu, Junchen; Almakimi, Abdulaziz; Wei, Mingzhen; Bai, Baojun; Ali Hussein, Ibnelwaleed
Abstract: In recent years, polymer micro/nanogels which are re-crosslinked polymers with 3D networks, have attracted a lot of interest in Enhanced Oil Recovery (EOR) field. In size of micro/nanometers, these gel particles are designed to be conformance control agents for in-depth fluid diversion, and various experimental research have been undertaken to investigate the possibilities of applying micro/nanogels in oilfield. However, it is still unclear that how to utilize micro/nanogels to their full potential in oilfield because the transport mechanisms and EOR mechanisms of micro/nanogels are not well studied currently. By reviewing experimental evaluations and corresponding results of micro/nanogels, including evaluation of particle physiochemical properties, transport, and potential EOR mechanisms, the review aims to discuss the evaluation of micro/nanogel particles, transport issue in many experimental designs and the debates of EOR mechanisms. Finally, we present the current challenges of micro/nanogels application and recommend the future research directions based on the review.